Effectiveness of pineapple peels as adsorbent for removal of Pb(II) / Nur Aziela Rozi - Rozi, Nur Aziela (2018)
There are many heavy metals are produced in wastewater by industries such as electroplating, electrolysis depositions, printed circuit board manufacturing wood processing petroleum and photographic operations. Heavy metals are dangerous to human body and environment. Human carcinogen will occur when human body exposed to the heavy metals and polluted to the environment. Heavy metals can enter human body through drinking. Therefore, heavy metals must be treated in wastewater before release in the environment. The objectives of this study are to determine the effectiveness of pineapple peels as the adsorbent in removal heavy metals and to study the characterization of the pineapple peels as adsorbent. In this study, the pineapple peels is prepared physically treated and chemically treated with acetic acid. The pineapple peels are prepared as non-calcined and calcined in this study by using temperature 105 for non-calcined while 300, 400 and 500 for calcined for physical treated and chemical treated and be characterized by Fourier transform infrared spectroscopy (FTIR) and Brunauer Emmett Teller (BET). The effect of pH, dosage and contact time are studied. The optimum pH for P300, P400, P500, C300, C400 and C500 are at pH 3 while P105 and C105 are at pH 4. The percentage removal of lead is achieved equilibrium at 50 minutes. The most effective adsorbent in this study is P300 with 99.70% removal of lead ion from solution at pH 3 with 0.1g of adsorbent shaken for 15 minutes.